Assessment of primary cocoa beans processing methods in Owan west local government area of Edo State, Nigeria (2007)
This study assessed the primary cocoa beans processing methods in Owan West Local Government Area (OWLGA) of Edo State, Nigeria. Systematic random sampling was used in selecting 125 farmers in three main cocoa producing communities of OWLGA. Data were collected with structured questionnaire and analyzed using descriptive statistics and Pearson correlation. Age range for majority (56%) of the respondents was 55-68 and 69-82 years. Many (59.2%) cultivated small farms (< 2ha) and 48% had no formal education. All (100%) of sampled farmers identified heap and sun- drying processing methods while they were not aware of the sweat-box, tray and artificial drying methods. A high proportion (98.4%) processed cocoa beans in heaps and all (100%) used sun-drying method. Farm size (0.233) and identified processing methods (0.472) were significantly related to utilization of cocoa processing methods (p< 0.0 1). With adequate Government intervention, the common method (heap) used by farmers should be improved upon while tray method is popularized.